Pendampingan Pemasaran pada UMKM Kelurahan Muggut, Kecamatan Wungu, Kabupaten Madiun - Amri Amrulloh; Fachri Aditya (Gapenas Publisher, 2022)
Marketing is carried out in order to introduce products and services to potential consumers. MSMEs as supporting the country's economy also need marketing media to increase interest in potential buyers. This community service program is carried out on MSMEs in Madiun Regency, namely the Bengkel Truk Hartono and Warung Mbak Tut. The activity was carried out for 2 weeks from January 3 to 17, 2022. Finally the Bengkel Truk Hartono was assisted to create and use a membership program as a promotional step and Warung Mbak Tut used google my business as a marketing medium